1979
DOI: 10.1038/bjc.1979.255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biogenic amines on the growth of xenografted human colorectal carcinomas

Abstract: Summary.-The influence of some biogenic amines and amine-receptor-blocking drugs in the growth rate of human colorectal carcinomas propagated as s.c. xenografts in immune-deprived mice was studied. In mice treated with adrenaline, a /3-adrenergic agonist, the growth of xenografts was suppressed for 2 days, after which growth was resumed at a rate similar to that in control animals. Treatment with the phosphodiesterase inhibitor theophylline prolonged the adrenaline-induced inhibition of growth. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…These colonic carcinomas of mice thus appear to differ from those induced by the same carcinogen in rats and from naturally occurring human colonic tumours propagated as xenografts in immune-deprived mice, both of which appear to be inhibited by adrenaline but stimulated by certain other biogenic amines. (Tutton & Barkla, 1977;Tutton & Steel, 1979). In mouse colonic adenomas cell proliferation also appeared to be stimulated by adrenaline, but in this case the mechanism did not appear to involve either an alpha or a beta adrenoceptor.…”
Section: Discussionmentioning
confidence: 76%
“…These colonic carcinomas of mice thus appear to differ from those induced by the same carcinogen in rats and from naturally occurring human colonic tumours propagated as xenografts in immune-deprived mice, both of which appear to be inhibited by adrenaline but stimulated by certain other biogenic amines. (Tutton & Barkla, 1977;Tutton & Steel, 1979). In mouse colonic adenomas cell proliferation also appeared to be stimulated by adrenaline, but in this case the mechanism did not appear to involve either an alpha or a beta adrenoceptor.…”
Section: Discussionmentioning
confidence: 76%
“…PG E2 has been shown to elevate the intracellular levels of cyclic adenosine monophosphate (cAMP) (Kuehl et al, 1970) and the transient inhibition of xenograft growth in animals treated with the PG E2 analogue resembles the influences of adrenaline, also known to raise cellular cAMP levels (Sutherland & Rall, 1960) on the tumour HXK4 in xenograft (Tutton & Steel, 1979). The influence of adrenaline was prolonged by theophylline, an agent known to inhibit the enzyme phosphodiesterase, which degrades cAMP.…”
Section: Mitotic Rate In Ratmentioning
confidence: 99%
“…Some of the agents that have been shown to influence cell division in primary rat colonic tumours have now been shown to have a similar influence on human colonic tumours propagated as xenografts in immune-deprived mice (Tutton & Steel, 1979). However, the response to a particular agent varies markedly between each of the tissues examined.…”
mentioning
confidence: 99%
“…Adrenaline and other beta-adrenergic agonists have been shown to inhibit cell division in dimethylhydrazine-induced tumours of rat colon (Tutton & Barkla, 1977a), whereas histamine (acting via histamine-H2 receptors) and serotonin both promote cell division in these tumours (Tutton & Barkla, 1978a, b;1980a). By contrast noradrenaline, acting via an a-adrenergic receptor, promotes cell production in the colonic crypt epithelium (Tutton & Barkla, 1977a;Tutton & Steel, 1979) have shown that the growth rate of human colonic tumours propagated as xenografts in immune-deprived mice is also influenced by amine hormones. Growth of one tumour line, HXK4, a moderately to well differentiated colonic adenocarcinoma (Nowak et al, 1978) was inhibited by the histamine-H2-receptor antagonist, cimetidine, whereas another colonic tumour, HXK7 (a moderately to poorly differentiated colonic adenocarcinoma) was inhibited by an anti-serotoninergic drug, BW50Ic.…”
mentioning
confidence: 99%
“…Tumour Line HXK4, a moderately to well differentiated adenocarcinoma, originally described by Nowak et al (1978), was obtained from the Institute of Cancer Research, Royal Marsden Hospital (U.K.). This tumour line had previously been assessed as histamine-dependent, in the sense that its growth in immunedeprived mice was inhibited by administration of the histamine-H2-receptor antagonist Cimetidine (Tutton & Steel, 1979). Tumour Line HXM2 was established by the authors from a surgically resected specimen of descending colon tumour.…”
mentioning
confidence: 99%